Determination of some trace metals of mushrooms produced in middle Black Sea region of Turkey - Turhan, Kadir (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2007)
Trace metal levels in ten different mushroom species, Lactarius decipiens Quel., Lactarius piperatus, Lactarius resimus Fr., Lactarius valemus Fr., Lactarius vietus (Fr.) Fr., Laccaria lacceta, Agaricus bisporus, Agaricus silvicola, Lentinula edodes and Morchella deliciosa obtained from different areas of the middle Black Sea region of Turkey were determined by flame and graphite furnace atomic adsorption spectrometry after microwave digestion. The contents of trace metals in the mushroom samples were found in the ranges 74.21-127.70, 23444-49880, 69.51-99.93, 46.23-129.38, 3.69-27.51, 0.71-3.11, 0.41-1.57, 16.35-27.92, 3.54-29.87, 759-1200, 0.24-1.41, 8.69-22.41 and 0.13-0.54 mu g/g for Na, K, Ca, Fe, Cu, Pb, Cd, Zn, Mn, Mg, Cr, Ni, and Co, respectively. Results obtained are in agreement with trace data reported in the literature.
Keywords: mushrooms; environmental pollution; heavy metals; HEAVY-METALS; EDIBLE MUSHROOMS; FRUITING BODIES; SAMPLES; ELEMENTS; CADMIUM; COPPER; TOKAT; LEAD; Environmental Sciences & Ecology